Translational regulation by ribosome-associated quality control in neurodegenerative disease, cancer, and viral infection - Lu, Bingwei (Frontiers in Cell and Developmental Biology, 2022)
Translational control at the initiation, elongation, and terminations steps exerts immediate effects on the rate as well as the spatiotemporal dynamics of new protein synthesis, shaping the composition of the proteome. Translational control is particularly important for cells under stress as during viral infection or in disease conditions such as cancer and neurodegenerative diseases. Much has been learned about the control mechanisms acting at the translational initiation step under normal or pathological conditions. However, problems during the elongation or termination steps of translation can lead to ribosome stalling and ribosome collision, which will trigger ribosome-associated quality control (RQC) mechanism. Inadequate RQC may lead to the accumulation of faulty translation products that perturb protein homeostasis (proteostasis). Proteostasis signifies a cellular state in which the synthesis, folding, and degradation of proteins are maintained at a homeostatic state such that an intact proteome is preserved. Cellular capacity to preserve proteostasis declines with age, which is thought to contribute to age-related diseases. Proteostasis failure manifested as formation of aberrant protein aggregates, epitomized by the amyloid plaques in Alzheimer’s disease (AD), is a defining feature of neurodegenerative diseases. The root cause of the proteostasis failure and protein aggregation is still enigmatic. Here we will review recent studies supporting that faulty translation products resulting from inadequate RQC of translational stalling and ribosome collision during the translation of problematic mRNAs can be the root cause of proteostasis failure and may represent novel therapeutic targets for neurodegenerative diseases. We will also review evidence that translation regulation by RQC is operative in cancer cells and during viral infection. Better understanding of RQC mechanism may lead to novel therapeutic strategies against neurodegenerative diseases, cancer, and viral infections, including the ongoing COVID-19 pandemic.